Israel's restoration : a textual-comparative exploration of Ezekiel 36-39 - Crane, Ashley S. (Supplements to Vetus Testamentum, 2008)
Commentators traditionally use a textual-critical methodology in examining Hebrew and Greek manuscripts to establish an 'original' reading, frequently attributing other variants to scribal error. This book proposes a complementary-textual comparative methodology that treats each Hebrew and/or Greek manuscript with equal value.